Player Experience with Brazilian accent: development and validation of PX-BR, a summarized instrument in Portuguese - Aranha, Renan Vinicius; Nunes, Fátima L. S. (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2022: Anais do XVIII Simpósio Brasileiro de Sistemas de Informação, 2022)
Context: Evaluating player experience (PX) in digital games is naturally a complex process, being even more challenging when considering the linguistic and cultural factors. Problem: The main instruments available in the literature for PX evaluation are written in English, making their adoption with Brazilian users subject to translations and the potential uncertainty of users’ understanding. In addition, instruments usually contain a large number of statements, which can make them unfeasible to evaluate PX over time. Solution: This study presents the development and evaluation of an instrument in Brazilian Portuguese to assess the player's experience, containing three questions that summarize features related to immersion/presence, fun, and gameplay. IS Theory: Flow theory. Methods: With the collaboration of the Brazilian community of Games, Virtual Reality, and Human-Computer Interaction, three statements were defined to assess the components of immersion / presence, fun, and engagement, composing a summarized instrument. Then, an evaluation was performed with two games to analyze the correlation of the proposed instruments within the classic instruments from literature. Results: In addition to the construction of a new instrument, a validation process revealed that the statements of the new instrument present strong or moderate correlations with the information used as a reference. Contributions and Impact in the IS area: The research reported in this study contributes to the community by supporting the assessment of player experience in digital games, by proposing a new instrument focused on Brazilian users that can be used in studies that require repeated assessments through instruments.